Leaders in Mathematics Education Experience and Vision - Karp, Alexander; Roberts, David Lindsay; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2014)
This book consists of interviews with the most important mathematics educators of our time. These interviews were originally published in the International Journal for the History of Mathematics Education and are now being offered to a wider readership for the first time, collected in a single volume. Among the individuals interviewed are scholars from Brazil, France, Germany, Russia, the United Kingdom, and the United States who have made a significant impact on the development of mathematics education in their countries and internationally. The interviews cover their biographies, including their memories of their own studies in mathematics and their intellectual formation, their experience as researchers and teachers, and their visions of the history and future development of mathematics education. The book will be of interest to anyone involved in research in mathematics education, and anyone interested in the history of mathematics education.
Keywords: Education; Education; Education, general; Electronic books